DEVELOPMENT AND CHARACTERIZATION OF TOPICAL MICROEMULSION OF TRANEXAMIC ACID (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
The present study was performed to develop a topical microemulsion of the drug tranexamic acid (TXA) to help patients with hyperpigmentation. Microemulsion was made using dropwise addition method with the help of several surfactants and co-surfactants. The formulation was then evaluated for several parameters like clarity, particle size, drug diffusion etc. Drug Diffusion study was done using goat epidermal skin and at the end of the study it was found that the drug release was of 93.83%. Clarity of microemulsion was 98% and particle size and zeta potential of the formulation suggested it was a clear and stable system. To conclude, a promising drug delivery system for treatment of hyperpigmentation was developed and that it would help cosmetic market.